OCCLUSION OF NOBLE GASES (HE, NE, AR, KR, XE) INTO SYNTHETIC MAGNETITE AT 500-1300°C - Matsumoto T.; Maruo K.; Tsuchiyama A.; Matsuda J.I. (My University, 1996)
The trapping mechanism of noble gases during growth of magnetite is investigated by oxidizing Fe with water vapor at temperatures ranging from 500 to 1300oC. An apparent negative correlation between the concentration of argon and synthetic temperatures suggests that gases are trapped by adsorption. The fixation of adsorbed gas atoms is probably due to crystal growth. The elemental fractionation pattern of noble gases resembles so-called 'planetary type' patterns, with enrichments in heavier noble gases at high trapping temperatures. However, at lower temperatures, significant fractionation is not observed, reflecting a smaller absolute value of the negative heat of adsorption for lighter noble gases.The amount of argon in chondritic magnetite (Orgueil, CI) can be explained by adsorptive trapping of ambient noble gases at the suggested condensation temperature of magnetite in the solar nebular (# 400 K). 'Solar type' helium, neon and argon elemental ratios observed for the Orgueil magnetite are also qualitatively consistent with the results of the present experiments. Comparison experiments which synthesize magnetite with aqueous water are necessary for further discussion on the origin of the chondritic magnetite and its noble gases.
Keywords: NOBLE GASES; MAGNETITE; CONDENSATION; CHONDRITES; METEORITES